Review of Innovating Development Strategies in Africa, by Landry Signé - (:unkn) unknown (My University, 2018)
In Innovating Development Strategies in Africa, Landry Signé examines the processes that have led to the development of institutions and public policy in sub-Saharan Africa in the almost sixty years that have passed since independence. Signé uses nine West African francophone countries to explore the key drivers of Africa's transformation, the differences between countries, and the roles of the international, regional, and national actors involved. He focuses on innovations at the level of processes, explored through the study of four independent variables: ideas, interests, institutions, and time. He uses these variables to structure the four chapters that make up the main body of the book, preceded by two chapters describing the theoretical and methodological context of studying innovation in African economic development strategies. The final chapter summarizes the key conclusions of his research and proposes new approaches to analyzing change in political science. The concept of innovation that informs this book is broader than the usual definition taken by African and international actors to describe their development strategies. By this term, Signé refers not only to a change in the content of development strategies, but also to "the manner in which these changes in content emerge and are transformed, regardless of whether they are modest or radical" (p. 2). His key interest is in how these innovations occur. He supports the hypothesis that, though at a normative level some have observed an apparent continuity of development strategies, important innovations in process require attention. The book does a remarkable job of highlighting the differences and similarities among the countries studied and putting them into a broader context. These countries tend to be overlooked by anglophone researchers, making their presence here especially important. They can be divided into countries that entered independence with socialist-leaning economies (Benin
Keywords: African Research